Perancangan dan Pembuatan Aplikasi Pemeliharaan untuk Memantau Kondisi Mesin Pabrik Berbasis Android di PT. X - Riandy Winson; Henry Palit; Kristo Purba (Jurnal Infra, 2017)
Currently PT.X still uses manual recording in the form of physical documents to perform the maintenance process of the running machine. PT. X has several branches spread across several regions of the Territory of Indonesia, with business processes of product sales, raw material manufacturing and stock storage. Without using information system, accuracy and speed in processing and receiving data at PT. X and branches are also less good and require a longer time to do all activities in industry or office.With this application, users can also more easily in the process of checking the machine, valid checking data, checking reports and data integration is good. This application is also created using the programming language HTML, CSS, PHP, Javascript, Java and MySQL database. And for display applications using SB Admin template with Bootstrap support.The end result of the development of this application is the integration of company information is the recording of inspection reports items and data reports that have been verified based on a predetermined time and can more easily to know the current state of the machine condition.